Integrated Financial Information System and Mosque Profile Website: Digital Solutions for Administrative Efficiency and Promotion of Religious Activities at Attaufiq Gumuruh Mosque in Bandung - Alia Tri Utami; Sofa Parihah Nurasiah; Novita Nur Annisa; Made Budiramdani Kusuma (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2025)
Financial administration and promotion of religious activities at the Attaufiq Gumuruh Mosque in Bandung are still carried out manually, resulting in inefficiency, the risk of recording errors, and a lack of visibility of information to worshippers. This community service aims to develop an Integrated Financial Information System and Mosque Profile Website as a digital solution to improve administrative efficiency and optimize the promotion of activities. The research method uses a Research and Development (R&D) approach with stages of needs analysis, system design, implementation, testing (blackbox testing), and evaluation through questionnaires. In addition, this community service uses the Participatory Action Research (PAR) method through training and mentoring of mosque administrators and youth, involving the active participation of administrators in system development so that the system can be tailored to needs and be user-friendly. Functional testing results show that all features are running optimally, while user evaluations (administrators and congregations) show a satisfaction level of 89% in terms of ease of access and speed of service. The implementation of this system has been proven to increase financial transparency, reduce administrative burdens by 40%, and expand the reach of promotional activities through digital platforms. The combination of the financial system and the mosque profile website is an effective solution for the digital transformation of mosques, supporting accountable governance and active community participation. The community service conducted by a team of lecturers and students from Muhammadiyah University Bandung and Widyatama University recommends the need for regular training for mosque administrators and youth so that they can optimize the mosque profile website and web-based financial information system to increase donations and online fundraising campaigns